أثر سلوك المواطنة التنظيمية على جودة الخدمة المقدمة (Comprehensive Journal of Science, 2026)
This study aimed to identify the impact of organizational citizenship behavior on service quality. It was a field study conducted on faculty members at the Faculty of Commerce, Tarhuna, Zaytouna University. The study adopted a descriptive approach, and a questionnaire was developed in line with the objectives of the study and distributed to a sample of 45 individuals. The SPSS statistical program was used to analyze the questionnaire. SPSS statistical software was used to analyze the questionnaire. The study concluded with clear results confirming that organizational citizenship behaviors play an important role in improving the quality of educational services at the Faculty of Commerce, Al-Zaytouna University. The results of the statistical analysis showed that all the study's hypotheses were accepted with a high degree of significance, indicating that these behaviors are an active element in supporting academic and administrative performance within the faculty. The results of the main hypothesis test also showed a strong positive relationship between organizational citizenship behaviors, in their various dimensions, and the quality of educational services provided at the Faculty of Commerce. The study recommended that universities, especially Zaytouna University, should focus on promoting a culture of organizational citizenship within the university work environment by raising awareness of its importance and integrating it into academic and administrative training and development programs. It also emphasizes the importance of including the values of belonging, altruism, and professional commitment in the performance evaluation criteria for faculty members